The Assignment of Risks in Collaborative Construction Contracts - Figueroa Valdés, Juan Eduardo (2020)
This article examines in particular which are the risks inherent in any construction project, and from them, explains the risk assignment method used in traditional construction contracts, noting that it does not adequately solve the allocation of risks and attribution of blame, making construction projects more expensive. In response to how to face these difficulties, this paper studied the collaborative contracts, their common elements, classes and the way in which risks are distributed, making a detailed analysis of the collaborative contract par excellence, that is, the alliancing or Integrated Project Delivery, to finish carrying out a particular examination of how risk assignment is treated in standardized international construction contractual models, such as FIDIC, NEC and FAC-1 contracts.